Significance of chemical reaction and velocity slip on Magnetized Sutterby Nanofluid over Stretchable Sheet - K Srihari; B. Shankar Goud; T Lokesh Babu (Results in Engineering)
The novelty of current analysis is to examine various effects on steady Sutterby nanofluid flow over a stretching sheet. This communication describes the current mathematical modeling of Sutterby nanofluids with radiant heat assessment. Buongiorno's model incorporates the thermophoresis and Brownian motion effects. As part of the present study, velocity slip and magnetic fields were also studied in relation to flow phenomena. A Sutterby fluid model is used in order to represent the non-Newtonian nature. A boundary layer theory-based modeling framework is used to formulate the proposed model, which involves the use of basic partial differential equations that relate mass, momentum, energy, and nanoparticle concentration conservations. Based on similarity variables, we transformed the generated governing equations into ordinary differential equations. MATLAB's bvp4c code is used to handle the numerical treatment of the reduced system of ordinary differential equations. Through graph analysis, we determine and analyze the effects of different parameter characteristics on velocity, temperature, and concentration profiles. Tables are used to illustrate the physical consequences of governing factors, such as mass or heat transfer rate and skin friction. The main outcomes are: By increasing the power-low index, the velocity distribution is enhanced and fluid temperature is reduced. Upsurge in velocity-slip leads to a reduction in velocity distributions. Higher Deborah and Reynolds numbers increase velocity, whereas diminish the fluid temperature. Higher Thermophoresis values increase concentration and temperature. Higher Brownian motion values increase temperature and decline the concentration. Greater M, Re, and Ec values enhance temperature. Concentration profiles become thinner as the Schmidt number Sc and chemical parameters rise.